Efektywność i inne elementy przewagi konkurencyjnej przedsiębiorstwa oraz jej źródła - Czupiał, Jerzy (Efficiency and Other Elements of a Competitive Advantage of An Enterprise and its Sources, 2005)
Efficiency, quality, consumer responsiveness and innovation are all important elements in obtaining a competitive advantage. Sources of these elements are distinctive competencies of an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 64-69